Diversity of maize landraces of Nuevo León, México, using AFLP and morphological characters. - Rodríguez-Pérez, Gilberto (2012)
Diversity of maize landraces of Nuevo León, México, using AFLP and morphological characters. The objective of this work was to identify the molecular and phenotypicvariability among maize populations Pinto Amarillo and Liebre in Nuevo Leon, Mexico. The phenotypiccharacterization experiment was established in spring 2009.The variables registered were plant height, days to maleand female fl owering, number of rows per ear, kernels perrow of ears, length and diameter of the corn ear. For the molecular characterization of the 30 populations, the seedswere planted in February 2010 in pots with peat-moss. At30 days after planting all the leaves were collected and usedin AFLP. A cluster analysis was conducted using UPGMA method. Three groups were identified; twelve populations of Pinto Amarillo and three of Liebre. The landraces within each group were associated more to races of maize morethan to location.